ESTIMATION OF PLOIDY AND HYBRIDIZATION STATU8 BY ERYTHROCYTE AND NUCLEUS SIZE ANALYSIS IN CARPS - Nair, Vidya R.; Gopalkrishna, Gopalkrishna (Journal of Indian Fisheries Association, 2015)
The present experiment was designed to observe whether the nuclear volume and area are affected by the ploidy and hybrid status of the individual. Polyploidy was induced by heat shock treatment given at 44 Â± 0.5Â°C for 30 seconds and 45 seconds which was found to be most effective (64.7%) for induction of triploidy in Cyprinus carpio. Cell and nuclear volume and cell and nuclear area varied significantly in triploid fishes as compared to those of controls. Triploid fishes showed significantly higher growth compared to diploid counterparts. It was also observed that catla x rohu hybrid and its parents showed significant difference in the nuclear volume and area of their erythrocytes. Except nuclear volume, all the parameters were significantly different between catla and catla x rohu hybrid. The hybrids showed a closer relationship with catla as compared to rohu. Key words: Ploidy, hybridization, nucleus size